2004
DOI: 10.1111/j.1745-4514.2004.tb00074.x
|View full text |Cite
|
Sign up to set email alerts
|

Lipoperoxidation and Antioxidant Enzymes of Refrigerated Persian Limes (Citrus Latifolia Tanaka) as Influenced by a Prestorage Hot Treatment

Abstract: Effectiveness of a hot water dip conditioning (3 min, 53C) to prevent chilling injury was evaluated with Persian lime (Citrus latifolia Tanaka) fruits stored at 4, 8, 13 and 25C and 80% RH. Conditioning caused a significant increase in peroxidase and superoxide dismutase activities and lipoperoxidation levels in the flavedo of fruits immediately after treatment. During storage enzyme activities diminished until they reached control levels. Conditioned limes kept at 25C maintained higher lipoperoxidation levels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
1
3

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 31 publications
1
5
1
3
Order By: Relevance
“…Posmyk et al (2001) suggest that chilling sensitivity was associated with lipid peroxidation in germinating soybean seeds. However, previous results of our group in Persian limes do not support the idea that lipid peroxidation is the underlying mechanism for CI, because lipid peroxidation levels found in limes at chilling-inductive temperatures (4 and 8C) were similar to those found in a noninductive temperature (13C) (Rivera et al 2004). In the present study, higher levels of lipid peroxidation were observed at 4C (CI-inductive temperature).…”
Section: Discussioncontrasting
confidence: 83%
See 2 more Smart Citations
“…Posmyk et al (2001) suggest that chilling sensitivity was associated with lipid peroxidation in germinating soybean seeds. However, previous results of our group in Persian limes do not support the idea that lipid peroxidation is the underlying mechanism for CI, because lipid peroxidation levels found in limes at chilling-inductive temperatures (4 and 8C) were similar to those found in a noninductive temperature (13C) (Rivera et al 2004). In the present study, higher levels of lipid peroxidation were observed at 4C (CI-inductive temperature).…”
Section: Discussioncontrasting
confidence: 83%
“…According to several authors, CI tolerance was associated with the induction of antioxidant enzymes (CAT, SOD and APX) in conditioned fruits, and these increments were maintained along the cold storage period (Sala and Lafuente 1999; Kang and Saltveit 2001). In a previous work, we found that hot dipping (53C for 3 min) did not act as a protective treatment against CI of Persian limes, possibly because it was not able to sustain the increased antioxidant system during the entire storage period (Rivera et al. 2004).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…In such cases, a ROS attack on the unsaturated fatty acid chains of membrane lipids yields malondialdehyde (MDA) and 4-hydroxy alkenes (4-HAE), two products of fatty acid oxidation. In order to counteract the levels of ROS and maintain cellular homeostasis, cells possess both nonenzy-matic and enzymatic defense mechanisms acting in synchrony (Rivera et al 2004). The nonenzymatic system consists of various molecules of low molecular weight such as glutathione (GSH) and ascorbic acid (AsA), whereas the enzymatic system includes GSH peroxidase, catalase, superoxide dismutase and GSH reductase (GR), among other enzymes.…”
Section: Introductionmentioning
confidence: 99%
“…Embora a redução da sensibilidade ao frio tenha sido relatada em vários frutos submetidos a tratamentos térmicos, o possível mecanismo envolvido na indução de tolerância ao frio permanece ainda pouco compreendido. Alguns estudos têm atribuído tais benefícios à síntese de proteínas de choque térmico (HSP) em resposta ao estresse promovido pela exposição temporária dos frutos ao calor (VIERLING, 1991;LURIE;SABEHAT, 1997), enquanto outros sugerem que os tratamentos térmicos estimulam a atividade de enzimas antioxidantes, prevenindo a acumulação de radicais livres e o dano oxidativo aos tecidos (SALA; LAFUENTE, 1999;RIVERA, et al 2004;ZHANG et al, 2005;GASEMNEZHAD et al, 2008).…”
Section: Tecnologias Empregadas Na Pós-colheita Para Retardar O Desenunclassified